Uma experiência sobre a nutrição de Onychiurus cunhai Arlé, 1970 (Insecta, Collembola), com notas sobre sua ecologia - Rufino, Elisiana; Schubart, Herbert Otto (Acta Amazonica, 1974)
A new distribution is recorded in Manaus of Cnychiurus cunhai Arlé, 1970, which was previously known only from Belém. The conditions in which it is found, as in Belém, are in areas of drainage from primitive kitchens, where dirty water, rich in organic residue is thrown out, or runs out onto the ground. These conditions were simulated in the laboratory. Five cultures of the insect were raised on a humus sand substrate, with the addition, from time to time, of small amounts of sugar. These five cultures showed favourable results in survival, as compared with five control cultures to which no sugar was added. (Pig. 1, A & B). The cultures with sugar were the only cultures to have numerous progeny (Fig. 1, C). Evidently the addition of sugar stimulated the development of the micro-flora, the probable food basis of these Collembolans which feed on fine detritus. Further, it is suggested that the mass production of certain species, as described by Arlé (1970), occurs in disturbed places with a simplified biota, a high humidity and with easily decomposed organic matter. This enhances the growth of a rich microbial life in the soil, which can in turn, support large numbers of Collembolans. It is further suggested that during the heavy rains the insects are forced out of the soil because of water-logging which is severely prejudicial to them.